2018 15th IEEE Annual Consumer Communications &Amp; Networking Conference (CCNC) 2018
DOI: 10.1109/ccnc.2018.8319187
|View full text |Cite
|
Sign up to set email alerts
|

Towards a social virtual reality learning environment in high fidelity

Abstract: Virtual Learning Environments (VLEs) are spaces designed to educate students remotely via online platforms. Although traditional VLEs such as iSocial have shown promise in educating students, they offer limited immersion that diminishes learning effectiveness. This paper outlines a virtual reality learning environment (VRLE) over a high-speed network, which promotes educational effectiveness and efficiency via our creation of flexible content and infrastructure which meet established VLE standards with improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…The model provides the theoretical framework for this paper. As the technology has only recently enabled multimodal CVEs (Education, 2017), few empirical studies have addressed their impact on online learning (Isabwe, Moxnes, Ristesund, & Woodgate, 2018;Zizza et al, 2017). However, studies are yet to examine the impact of immersion (spatial, emotional and temporal) on the student subjective experiences and learning performance.…”
Section: :2mentioning
confidence: 99%
“…The model provides the theoretical framework for this paper. As the technology has only recently enabled multimodal CVEs (Education, 2017), few empirical studies have addressed their impact on online learning (Isabwe, Moxnes, Ristesund, & Woodgate, 2018;Zizza et al, 2017). However, studies are yet to examine the impact of immersion (spatial, emotional and temporal) on the student subjective experiences and learning performance.…”
Section: :2mentioning
confidence: 99%
“…Prior works on VRLEs have been developed for immersive and special education purposes. In vSocial [1], a Social Competence Intervention (SCI) curriculum [3] is delivered via a system that consists of various modules such as: VR rendering, web applications and classroom portal with instructional content hosted as web pages. The vSocial server provides functionalities such as access control for users, session management, network performance tracking, session progress, and user management, making it a critical target in the system.…”
Section: A Virtual Reality Learning Environmentsmentioning
confidence: 99%
“…The results indicated that the immersive condition and the positive emotional induction can influence knowledge retention. Zizza et al [18] designed and implemented a multimodule VR learning environment over the network. They evaluated user experience in the VR version by comparing it to a desktop version.…”
Section: Use Case Studies Of Serious Vr Gamesmentioning
confidence: 99%